Clinicopathological Features Associated with Lymph Node Metastasis in Early Gastric Cancer: Analysis of a Single-Institution Experience in China - Lizong Shen; Yiming Huang; Maocai Sun; Hao Xu; Wei Wei; Wenxi Wu (Canadian Journal of Gastroenterology)
BACKGROUND: An accurate assessment of potential lymph node metastasis is an important issue for the appropriate treatment of early gastric cancer. Minimizing the number of invasive procedures used in cancer therapy is critical for improving the patient’s quality of life.